1988
DOI: 10.1016/0035-9203(88)90041-7
|View full text |Cite
|
Sign up to set email alerts
|

A zymovar analysis of Vibrio cholerae isolated in Australia

Abstract: Zymovar analysis was used to study 50 strains of Vibrio cholerae O1 and 40 strains of V. cholerae non-O1 isolated in Australia. The strains were assigned to 42 zymovars; the O1 strains to 9 types and the non-O1 strains to 33 types, with no overlapping between serovars. All the human O1 isolates, regardless of their ability to produce cholera toxin (CT), and all the CT-producing O1 environmental isolates, were type Z14. The remaining O1 strains and the non-O1 strains belonged to a variety of zymovars, and more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0
1

Year Published

1991
1991
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 7 publications
2
13
0
1
Order By: Relevance
“…The high degree of genotypic and phenotypic similarity between human and environmental isolates is consistent with V. cholerae 01 survival and persistence in the environment. A recent report from Australia also indicated that toxigenic V. cholerae 01 from humans and from the environment belong in the same zymovar [30].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The high degree of genotypic and phenotypic similarity between human and environmental isolates is consistent with V. cholerae 01 survival and persistence in the environment. A recent report from Australia also indicated that toxigenic V. cholerae 01 from humans and from the environment belong in the same zymovar [30].…”
Section: Resultsmentioning
confidence: 99%
“…MEE has been used in several studies of V. cholerae O1 and non-O1 as well as other Vibrio species. These studies examined only a few enzymes and few isolates [30][31][32][33], did not specifically address the relationships within the V. cholerae 01 group, and did not include isolates from the Gulf of Mexico region.…”
Section: Introductionmentioning
confidence: 99%
“…(1995) applied ribotyping to differentiate V. cholerae non‐O1 isolated from shrimp farms in Thailand. The genetic diversity of V. cholerae was determined by multilocus enzyme electrophoresis (Desmarchelier et al. 1988; Chen et al.…”
Section: Introductionmentioning
confidence: 99%
“…Dalsgaard et al (1995) applied ribotyping to differentiate V. cholerae non-O1 isolated from shrimp farms in Thailand. The genetic diversity of V. cholerae was determined by multilocus enzyme electrophoresis (Desmarchelier et al 1988;Chen et al 1991), ribotyping (Koblavi et al 1990;Karaolis et al 1994), pulsed-field gel electrophoresis (Cameron et al 1994) and amplified fragment length polymorphism fingerprinting (Jiang et al 2000). Despite the extensive applicability of these techniques, their use has been limited, because they are time-consuming and labour intensive.…”
Section: Introductionmentioning
confidence: 99%
“…Since the first indigenous cholera case occurred in southeast Queensland in 1977, sporadic human cases have occurred periodically within Australia, and extensive epidemiological and ecological studies have isolated Vibrio cholerue 01 from at least 13 river systems along the east coast of Australia in the absence of any significant human or animal reservoirs [lO,ll]. Analysis of local 01 isolates by means of their biovars, serovars, phage-typing patterns Ill], zymovars [12], CWRFLP, and total chromosomal-RFLP [13] has shown them to be a diverse, and predominantly toxigenic, group. GP156 (biotype El Tor, serotype Inaba) was isolated from a riverine environment in southeast Queensland, Australia [8].…”
Section: Introductionmentioning
confidence: 99%